A sodium-ion battery and a preparation method thereof
Patent Information
- Application Number
- CN202610301459.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-12
- Publication Date
- 2026-10-23
AI Technical Summary
然而,其未考虑到负极极片真实电导率对电池性能的影响
[0053]本发明提供的一种钠离子电池及其制备方法的有益效果:本发明的钠离子电池的电解液中加入钠盐型添加剂和含硫添加剂,并控制负极极片的孔隙率和麦克马林数,能够协同性地优化钠离子电池SEI膜的组成和极片中离子通道的导通性,有效降低电池整体的内阻,提升电池循环性能,使钠离子电池既能够优化电池在低温环境和长循环运行时的不足,同时兼顾钠离子电池的高温性能,最终得到宽温优异的长循环钠离子电池。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of sodium-ion battery technology, and in particular to a sodium-ion battery and its preparation method. Background Technology
[0002] Sodium-ion batteries, due to their abundant resources and low cost, are expected to be widely used in various fields such as large and small power sources, emergency power supplies, scientific exploration in high-latitude regions, and large-scale energy storage. However, existing sodium-ion batteries struggle to simultaneously achieve high and low temperature performance. At low temperatures, electrochemical reaction kinetics slow down, interfacial impedance increases, and capacity decays, requiring a thin interfacial film with low initial impedance. At high temperatures, however, thin SEI films exhibit poor stability and are prone to decomposition, rupture, and recombination, leading to continuous consumption of active sodium and increased battery internal resistance, thus shortening cycle life.
[0003] CN202410116612.0 discloses an ultra-low temperature high-energy-density sodium-ion battery and its preparation method, which mainly improves the low-temperature performance of the sodium-ion battery by adjusting the electrolyte additives and the average pore radius of the positive and negative electrode active material layers. However, it does not consider the impact of the actual conductivity of the negative electrode on battery performance. During ultra-low temperatures and long-term cycling, the actual conductivity of the negative electrode, without measurement and adjustment of the McMurlin number, may be insufficient. Under the bottleneck effect, the rapid movement of ions within the microstructure of the negative electrode cannot be guaranteed, resulting in poor low-temperature performance of the battery. Specifically, conduction hindrance within the electrode leads to increased polarization and charge accumulation at the negative electrode interface. This not only increases the risk of sodium deposition and side reactions, but may also eventually lead to a decrease in the coulombic efficiency and rapid capacity decay of the battery. Although it has taken into account that the ion transport path of the high-porosity negative electrode is better, it will reduce the energy density; although the low-porosity compacted electrode can improve the energy density, it will seriously deteriorate the ion transport capability. A certain balance has been made between them, but the impact of the actual conductivity of the electrode on the battery performance has not been taken into account and this bottleneck effect has not been avoided. The battery cannot take into account the high-temperature performance of sodium-ion batteries in low-temperature environments and long-cycle operation.
[0004] Therefore, developing a wide-temperature-range sodium-ion battery with excellent high and low temperature performance is a technical challenge that urgently needs to be solved. Summary of the Invention
[0005] This invention provides a sodium-ion battery that can significantly improve the low-temperature charge and discharge performance of sodium-ion batteries and meet the requirements for high-temperature use.
[0006] In a first aspect, the present invention provides a sodium-ion battery, comprising a positive electrode, a negative electrode, and an electrolyte, wherein the electrolyte comprises a sodium salt additive and a sulfur-containing additive, and the sodium-ion battery satisfies the following relationship: 2.1≤C / [100×(A+B)]+M1 / 2 ≤5.2; In the formula: A represents the mass percentage of sodium salt additives in the electrolyte, where 0.1% ≤ A ≤ 2%. B represents the mass percentage of sulfur-containing additives in the electrolyte, where 0.1% ≤ B ≤ 2%. C represents the porosity of the negative electrode sheet, where 25% ≤ C ≤ 50%. M is the McMallin number of the negative electrode, also known as the capillary tortuosity factor, 4≤M≤25.
[0007] The sodium-ion battery of this invention introduces a suitable combination of sodium salt additives and sulfur-containing additives into the electrolyte (excessive sodium salt additives have limited solubility and will form crystalline solids in the electrolyte, endangering battery safety; excessive sodium salt additives have insufficient film-forming effect; excessive sulfur-containing additives cause the interface film to be too thick, increase initial impedance, and exacerbate gas production, which needs to be limited to a certain extent; similarly, low content leads to insufficient beneficial effects), and controls the porosity and McMurlin number of the negative electrode in the sodium-ion battery to satisfy the above relationship (high porosity negative electrode has better ion transport, but will reduce energy density; low porosity compacted electrode can improve energy density, but will seriously deteriorate ion transport capability and electrolyte wettability, considering the actual conductivity of the electrode characterized by the McMurlin number for the battery). The impact of performance is weighed against the impact of porosity to avoid the negative electrode becoming a bottleneck in ion conduction within the battery. Through exploration and testing, the above formula composition and parameter limits can synergistically optimize the composition of the SEI film and the conductivity of ion channels in the electrode within the conventional range achievable in the industry without significantly increasing costs. This results in an SEI film with low initial impedance, low impedance growth rate, and good ion permeability at low temperatures. This improves the conductivity of the electrolyte and the diffusion and transport rate of ions in the negative electrode, effectively reducing the overall internal resistance of the battery and improving the battery cycle performance. As a result, the sodium-ion battery can both optimize the shortcomings of the battery in low-temperature environments and long-cycle operation, and also take into account the high-temperature performance of the sodium-ion battery, ultimately obtaining a long-cycle sodium-ion battery with excellent wide-temperature performance.
[0008] In this invention, the porosity of the negative electrode sheet can be determined using conventional porosity measurement methods. In one optional embodiment of this invention, the porosity of the negative electrode sheet is determined using a liquid absorption method (or electrolyte immersion method). Specific steps include: immersing a negative electrode sheet sample of known size and dry weight in an inert organic solvent (such as n-decane) or electrolyte under vacuum conditions until its pores are completely saturated; removing the sample, drying the surface, and weighing the wet weight; and calculating the porosity using the solvent density, the apparent volume of the sample, and the electrode skeleton density.
[0009] In one optional specific embodiment of the present invention, the specific testing steps for the porosity of the negative electrode sheet are as follows: The negative electrode sheet sample, whose cross-sectional area and thickness have been measured, is vacuum dried at 80°C for 12 hours, and its dry weight (m³) is then measured. dry The sample was then completely immersed in the inert organic solvent n-decane and allowed to stand under vacuum until saturation adsorption. After removal, the surface solvent was quickly wiped off, and its wet weight (m) was recorded. wet Porosity C is calculated using the following formula: C = 100% × (m wet- m dry ) / (ρ 正癸烷 ×A×t); In the formula: m dry Dry weight refers to the mass of the negative electrode sample to be tested after it has been fully dried in a vacuum oven, in grams. m wet Wet weight refers to the mass of the dried negative electrode sample after it has been completely immersed in n-decane under vacuum until it is saturated with adsorption. The sample is then removed, and the surface residue is quickly wiped clean with filter paper before weighing. The unit is g. ρ 正癸烷 Liquid density refers to the density of n-decane at the test temperature, in g / cm³. 3 The room temperature is 0.73 g / cm³. 3 ; A: Cross-sectional area of the negative electrode sample, unit: cm² 2 ; t: Thickness of the negative electrode sample, in cm; C: Porosity of the negative electrode sheet, referring to the open porosity of the negative electrode sheet, that is, the percentage of the pore volume that the electrolyte can fill to the total volume of the negative electrode sheet, in units of: .
[0010] The value of M can be calculated using the following formula: M = C × κ0 / κ_eff = (Le / t) 2 =τ 2 ; In the formula: C: Porosity, referring to the porosity of the negative electrode sheet; it represents the proportion of space where ions can "walk". The higher the porosity (the larger the C), the more ion channels there are theoretically. It is measured using the same method as described above for detecting the porosity of the negative electrode sheet.
[0011] κ0: Bulk conductivity, referring to the conductivity of the electrolyte used in the battery itself. It represents the speed at which ions move in "open space". It is obtained by measuring the conductivity of the electrolyte at 25°C using a conductivity meter.
[0012] κ_eff: Effective conductivity, refers to the overall conductivity exhibited by ions when they actually penetrate a membrane or porous electrode structure saturated with electrolyte. It comprehensively reflects the true transport efficiency under the combined effects of porosity and tortuosity. Test method: The negative electrode sample to be tested is immersed in the electrolyte until it is completely saturated, and a symmetrical cell is assembled. Using an electrochemical workstation, AC impedance spectroscopy is performed on the symmetrical cell in the high-frequency region (usually 10 kHz to 1 MHz). The portion of the Nyquist plot that intersects the real axis in the high-frequency region is the bulk resistance (Rb). The thickness t (unit: cm) and cross-sectional area A (unit: cm²) of the negative electrode sample are measured. 2 Effective conductivity κ_eff = L / (Rb×A) (unit: mS / cm).
[0013] τ: This refers to the ratio between the actual path length (Le) of the ions and the physical thickness (t) of the battery separator or electrode. τ is always greater than 1, and the larger the value, the longer the ions "take a detour." The actual path ions take refers to the path they take from the solution through the SEI into the three-dimensional negative electrode sheet, and then through the pores of the electrode sheet to reach the surface of the negative electrode material where they are embedded.
[0014] Furthermore, the sodium-ion battery satisfies the following relationship: 2.4 ≤ C / [100×(A+B)]+M 1 / 2 ≤3.4; 0.5%≤A≤1.0%, 0.5%≤B≤1.0%, 35%≤C≤50%, 5≤M≤10.
[0015] Furthermore, the mass ratio of the sodium salt additive to the sulfur-containing additive is 0.33~3.0:1. The sodium salt additive helps to form an SEI film with low initial impedance, low impedance growth rate, and good low-temperature permeability, thus optimizing the shortcomings of the battery in low-temperature environments and long-cycle operation; the sulfur-containing additive can improve the high-temperature performance of sodium-ion batteries. When the two are combined in the above mass ratio, the sodium-ion battery can achieve better charge-discharge performance and cycle life under both high and low temperature conditions.
[0016] Furthermore, the sulfur-containing additive includes at least one of cyclic sulfate compounds and cyclic sulfonate compounds.
[0017] Preferably, the cyclic sulfate compound includes at least one selected from ethylene sulfate, propylene sulfate, 4-methylethylene sulfate, 4-fluoroethylene sulfate, 4,4'-diethylene sulfate, spirodiDTD, bis(DTD), 4,5-dimethylethylene sulfate, and 1,2-cyclopentadiene sulfate.
[0018] Preferably, the cyclic sulfonate compound includes at least one of 1,3-propanesulfonate lactone, 1,3-propenesulfonate lactone, and methanedisulfonate methylene ester.
[0019] Preferably, the sulfur-containing additive is selected from at least one of ethylene sulfate, propylene sulfate, 1,3-propanesulfonate lactone, 1,3-propenesulfonate lactone, and methanedisulfonate. This invention has found that when at least one of ethylene sulfate, propylene sulfate, 1,3-propanesulfonate lactone, 1,3-propenesulfonate lactone, and methanedisulfonate is used as the sulfur-containing additive, the charge-discharge performance and cycle life of sodium-ion batteries at high temperatures can be better improved.
[0020] Furthermore, the sodium salt type additive includes at least one of sodium oxalate borate, sodium difluorophosphate, sodium difluorodioxalate phosphate, and sodium fluorosulfonate.
[0021] Preferably, the sodium oxalate borate salt comprises sodium bis(oxalate borate); Preferably, the sodium salt additive is selected from at least one of sodium fluorosulfonate and sodium difluorodioxazophosphate.
[0022] R SEI The SEI (Sediment Inlet) impedance is a crucial component of battery impedance. A high SEI impedance significantly inhibits the process of sodium ions penetrating the SEI and diffusing into the solid at low temperatures, thus hindering the formation of internal current. Macroscopically, this manifests as the battery being unable to operate at excessively high rates or excessively low temperatures. This invention, by employing negative electrode sheets with specific porosity and McMurlin numbers, and by designing and combining different types and amounts of sodium salt additives and sulfur-containing additives, can further significantly improve the low-temperature charging performance of sodium-ion batteries, while also enhancing cycle life. Specifically, this invention constructs an inorganic component structure rich in elements such as boron, fluorine, and phosphorus in the SEI membrane and optimizes its spatial structure by controlling the type and amount of sodium salt additives and sulfur-containing additives, thereby enhancing the permeability of sodium ions. At the same time, it is paired with a negative electrode sheet with suitable porosity and tortuosity (characterized by McMullin number), which increases the proportion of space through which ions can pass at the electrode angle, reduces the ineffective paths that ions need to take for diffusion, improves the effective conductivity of the electrolyte in the electrode sheet, and ensures the rapid movement of ions at the microstructure level within the electrode sheet. In addition, the sulfur-containing additives can also improve the high-temperature performance of the sodium-ion battery, so that the prepared sodium-ion battery can meet both low-temperature charge and discharge performance and high-temperature use requirements.
[0023] Furthermore, the electrolyte also includes ester solvents, which include cyclic carbonate solvents, chain carbonate solvents, and linear carboxylic acid ester solvents in a volume ratio of 20~40:20~40:10~60.
[0024] Preferably, the cyclic carbonate solvent includes at least one of ethylene carbonate, propylene carbonate, and γ-butyrolactone.
[0025] Preferably, the chain carbonate solvent includes at least one of dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.
[0026] Preferably, the linear carboxylic acid ester solvent includes at least one of methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, and methyl butyrate.
[0027] Preferably, the ester solvent is composed of propylene carbonate, methyl ethyl carbonate, and ethyl acetate. This invention has found that when propylene carbonate, methyl ethyl carbonate, and ethyl acetate are used in combination, both the low-temperature charge-discharge performance of sodium-ion batteries and the high-temperature performance requirements can be met. In the electrolyte system of this invention that satisfies the specific formula described above, a better balance between the low-temperature and high-temperature performance of sodium-ion batteries can be achieved, resulting in a better improvement in both performance.
[0028] Furthermore, the electrolyte also includes an electrolyte salt, the electrolyte salt having a mass percentage content of 10-15% in the electrolyte.
[0029] Preferably, the electrolyte salt includes at least one of sodium hexafluorophosphate, sodium tetrafluoroborate, sodium perchlorate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethanesulfonyl)imide.
[0030] Preferably, the electrolyte salt is composed of sodium hexafluorophosphate and sodium difluorosulfonamide in a mass ratio of 0.5 to 2:1.
[0031] Furthermore, the electrolyte also includes conventional additives, the conventional additives comprising 0.5 to 2.5% by mass in the electrolyte.
[0032] Preferably, the conventional additives include at least one of vinylene carbonate, fluoroethylene carbonate, vinyl ethylene carbonate, and sodium difluorooxalate borate.
[0033] Preferably, the conventional additive consists of sodium difluorooxalate borate and fluoroethylene carbonate in a mass ratio of 1:1 to 3. Controlling the sodium difluorooxalate borate and fluoroethylene carbonate within this range allows for the formation of the basic SEI membrane components, ensuring fundamental performance.
[0034] Furthermore, the negative electrode sheet includes a negative current collector and a negative active material layer formed on the surface of the negative current collector. By mass percentage, the negative electrode slurry used to form the negative active material layer includes 93-97% negative active material, 0.5-5% negative conductive agent, 0.5-5% negative thickener, and 0.5-3% negative binder.
[0035] Furthermore, the negative electrode current collector is selected from any one of the following: a metal material capable of conducting electrons, a carbon-coated metal foil, or a porous metal plate, such as at least one of aluminum, nickel, tin, copper, and stainless steel. Copper or aluminum is preferred.
[0036] Furthermore, there are no particular limitations on the negative electrode active material; any conventional negative electrode active material in the art can be used, such as any one of carbon-based materials, titanium-based materials, alloy materials, organic compound materials, etc., such as hard carbon.
[0037] Furthermore, the negative electrode conductive agent is used to improve the conductivity of the negative electrode active material layer. The present invention does not limit the type of negative electrode conductive agent, and it can be selected according to actual needs. For example, it can be at least one of super conductive carbon black, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0038] Furthermore, the negative electrode adhesive is also a conventional negative electrode adhesive in the art, which can be selected according to actual needs, such as at least one of styrene-butadiene rubber, styrene-butadiene rubber, waterborne acrylic resin and carboxymethyl cellulose.
[0039] Furthermore, the negative electrode thickener is also a conventional negative electrode thickener in the art, such as carboxymethyl cellulose or sodium carboxymethyl cellulose.
[0040] Preferably, in one of the optional embodiments of the present invention, the negative electrode slurry includes hard carbon, SuperP (super conductive carbon black), CMC (sodium carboxymethyl cellulose) and SBR (styrene-butadiene rubber), and the negative electrode current collector is aluminum foil.
[0041] Furthermore, in the preparation of the negative electrode active material layer, the negative electrode active material, negative electrode conductive agent, negative electrode thickener and negative electrode binder are first mixed and dispersed in water to obtain a negative electrode slurry. Then, the negative electrode slurry is coated on the surface of the negative electrode current collector, and then dried and pressed.
[0042] Preferably, in the preparation of the negative electrode slurry, the negative electrode active material, negative electrode conductive agent and negative electrode thickener are first dispersed in water, then the slurry is subjected to high-speed shearing treatment, and then the negative electrode binder is added and mixed evenly.
[0043] Preferably, the parameters for the high-speed shearing process are: linear velocity of 15-20 m / s and high-speed shearing time of 10-20 minutes.
[0044] Furthermore, the positive electrode sheet includes a positive current collector and a positive active material layer formed on the surface of the positive current collector. The positive slurry used to form the positive active material layer contains a positive active material, a positive conductive agent, and a positive binder. The positive active material accounts for 85% to 95% of the mass of the positive slurry, the positive conductive agent accounts for 3% to 12% of the mass of the positive slurry, and the positive binder accounts for 2% to 6% of the mass of the positive slurry.
[0045] Furthermore, the positive current collector is selected from a metallic material that can conduct electrons, and the metallic material that can conduct electrons includes at least one of aluminum, nickel, tin, copper and stainless steel, preferably aluminum.
[0046] Furthermore, there are no particular limitations on the positive electrode active material; any conventional positive electrode active material in the art can be used, such as layered metal oxides, polyanionic compounds, Prussian blue compounds, or Prussian white compounds.
[0047] Furthermore, the positive electrode adhesive is not particularly limited, and any conventional positive electrode adhesive in the art can be used. For example, it can be at least one of thermoplastic resin, acrylic resin, sodium carboxymethyl cellulose, and styrene-butadiene rubber. The thermoplastic resin includes at least one of polyvinylidene fluoride, copolymers of polyvinylidene fluoride, polytetrafluoroethylene, copolymers of polyvinylidene fluoride-hexafluoropropylene, copolymers of tetrafluoroethylene-hexafluoropropylene, copolymers of tetrafluoroethylene-perfluoroalkyl vinyl ether, copolymers of ethylene-tetrafluoroethylene, copolymers of polyvinylidene fluoride-tetrafluoroethylene, copolymers of polyvinylidene fluoride-trifluoroethylene, copolymers of polyvinylidene fluoride-trichloroethylene, copolymers of polyvinylidene fluoride-fluorinated ethylene, copolymers of polyvinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, polyethylene, and polypropylene.
[0048] Furthermore, the positive electrode conductive agent includes at least one of super conductive carbon black, conductive carbon spheres, conductive graphite, conductive carbon fiber, carbon nanotubes, graphene, and reduced graphene oxide.
[0049] Preferably, in one of the optional embodiments of the present invention, the positive electrode slurry includes a positive electrode active material (CFM012R, Zhongke Haina Technology Co., Ltd.), SuperP and PVDF (polyvinylidene fluoride), and the positive electrode current collector is aluminum foil.
[0050] In the preparation of the positive electrode active material layer, the positive electrode active material, positive electrode binder and positive electrode conductive agent are first mixed and dispersed in N-methylpyrrolidone (NMP) to obtain a positive electrode slurry. Then the positive electrode slurry is coated on the surface of the positive electrode current collector, and then dried and pressed.
[0051] Furthermore, the sodium-ion battery also includes a separator. The type of separator is not limited. Any well-known porous structure separator with electrochemical and mechanical stability can be selected according to actual needs. For example, it can be a single-layer or multi-layer film containing at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride.
[0052] In a second aspect, the present invention provides a method for preparing the above-mentioned sodium-ion battery, comprising the following steps: assembling the positive electrode, the separator and the negative electrode into a bare cell, injecting the electrolyte, and then performing encapsulation and formation processes.
[0053] The beneficial effects of the sodium-ion battery and its preparation method provided by this invention are as follows: The sodium-ion battery of this invention adds sodium salt additives and sulfur-containing additives to the electrolyte, and controls the porosity and McMurlin number of the negative electrode sheet. This can synergistically optimize the composition of the SEI film of the sodium-ion battery and the conductivity of the ion channels in the electrode sheet, effectively reduce the overall internal resistance of the battery, improve the battery cycle performance, and enable the sodium-ion battery to optimize the shortcomings of the battery in low temperature environment and long cycle operation, while taking into account the high temperature performance of the sodium-ion battery, and finally obtain a long cycle sodium-ion battery with excellent wide temperature range. Detailed Implementation
[0054] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0055] Where specific techniques or conditions are not specified in the examples, they shall be performed in accordance with the techniques or conditions described in the literature in this field, or in accordance with the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased through legitimate channels.
[0056] The following are some raw material information for the examples and comparative examples: Cathode active material: CFM012R, Zhongke Haina Technology Co., Ltd.; PVDF: Zhejiang Fluorol® FL2001 PVDF; CMC: Specification BH90-Ⅱ, Changshu Weiyi Technology Co., Ltd. SBR: Shengxi'ao SBR, Voltabond™ series, Shenzhen Taineng New Materials Co., Ltd.; Hard carbon: Shandong Shengquan New Energy Technology Co., Ltd.; SuperP: Jiangxi Jinxi Nanomaterials Co., Ltd.
[0057] The abbreviations and full names of the raw materials used in the following examples and comparative examples are as follows: SuperP: Super conductive carbon black; PVDF: Polyvinylidene fluoride; CMC: Sodium carboxymethyl cellulose; SBR: Styrene-butadiene rubber; PC: Propylene carbonate; EMC: Ethyl methyl carbonate; EA: Ethyl acetate; PP: Propyl propionate; EP: Ethyl propionate; DFOB: Sodium difluorooxalate borate; FEC: Fluoroethylene carbonate; NaPF6: Sodium hexafluorophosphate; NaFSI: Sodium difluorosulfonyl imide; NaFOS: Sodium fluorosulfonate; NaDFOP: Sodium difluorooxalate borate; PCS: Propylene sulfate; MMDS: Methylene disulfonate; PS: 1,3-propanesulfonate lactone; DTD: Ethyl sulfate.
[0058] Example 1 This embodiment provides a sodium-ion battery, including a positive electrode, a negative electrode, a separator, and an electrolyte. The positive electrode includes a positive current collector (aluminum foil) and a positive active material layer formed on the surface of the positive current collector (aluminum foil). The positive electrode slurry used to form the positive active material layer contains a positive active material (CFM012R), a conductive agent (SuperP), and a binder (PVDF). The positive active material accounts for 90% of the mass of the positive electrode slurry, SuperP accounts for 6% of the mass of the positive electrode slurry, and PVDF accounts for 4% of the mass of the positive electrode slurry.
[0059] The negative electrode sheet includes a negative current collector (aluminum foil) and a negative active material layer formed on the surface of the negative current collector (aluminum foil). The negative electrode slurry used to form the negative active material layer contains hard carbon (active material), SuperP (conductive agent), CMC (thickener) and SBR (binder). By mass percentage, the negative electrode slurry includes 94.3% hard carbon, 1.4% SuperP, 1.6% CMC and 2.7% SBR.
[0060] The composition of the electrolyte is shown in Table 1.
[0061] This embodiment also provides a method for preparing the above-mentioned sodium-ion battery, the steps of which are as follows: (1) Preparation of positive electrode sheet: The positive active material (CFM012R), SuperP and PVDF are mixed and uniformly dispersed in sufficient N-methylpyrrolidone to obtain a positive electrode slurry (the solid content in the positive electrode slurry is 50%). Then the positive electrode slurry is coated on the positive current collector (aluminum foil), dried and pressed to obtain a positive electrode sheet.
[0062] (2) Preparation of negative electrode sheet: Hard carbon, SuperP and CMC were uniformly dispersed in deionized water at a speed of 200-400 rpm for 60 minutes. Subsequently, the slurry was subjected to high-speed shearing treatment at a linear velocity of 18 m / s for 15 minutes using a high-speed disperser. Then, SBR was added and mixed at a low speed of 50 rpm for 30 minutes to obtain a negative electrode slurry (the solid content in the negative electrode slurry was 48%). The negative electrode slurry was then coated onto a negative electrode current collector (aluminum foil) with a wet film thickness of 100 μm, dried at 80℃, and pressed to obtain a negative electrode sheet. The mass ratio of hard carbon, SuperP, CMC and SBR was 94.3:1.4:1.6:2.7.
[0063] (3) Preparation of electrolyte: Mix the raw materials according to the proportions in Table 1 to obtain the electrolyte.
[0064] (4) Assemble sodium-ion batteries: Stack the positive electrode, separator, and negative electrode in sequence, so that the separator is in the middle of the positive electrode and the negative electrode to play a role in isolation. Then, wind them to obtain bare cells. Place the bare cells in a 40160 steel shell outer packaging, inject electrolyte, and seal and form to obtain sodium-ion batteries.
[0065] In this embodiment, the method for determining the porosity C of the negative electrode sheet is as follows: A square sample with dimensions of 5.0 cm × 5.0 cm was cut from the negative electrode sheet. Its average thickness t was measured to be 100 μm (0.01 cm) using a thickness gauge, and its cross-sectional area A was 25 cm². 2 .
[0066] The cut square negative electrode sample was placed in an 80℃ vacuum oven and dried for 12 hours. After removal, it was weighed quickly, and its dry weight m was recorded. dry The concentration was 0.3 g. The dried negative electrode sample was completely immersed in the inert solvent n-decane (density ρ = 0.73 g / cm³). 3 In the process, the sample was allowed to stand under vacuum for 2 hours to ensure complete pore saturation. The saturated negative electrode sample was then removed, the surface was quickly wiped clean of any residual solvent, and its wet weight (m) was immediately measured. wet It is 0.364 g. According to the formula for porosity C: C = 100% × (m² / g) wet- m dry ) / (ρ 正癸烷 ×A×t)=(0.364g- 0.300 g) / 0.73 g / cm 3 / (25 cm) 2 (× 0.010 cm) × 100% = 35%.
[0067] The method for determining the McMurline number of the negative electrode is as follows: The above electrolyte was measured using a conductivity meter at 25°C, and the bulk conductivity κ0 was found to be 9.53 mS / cm. Impedance test: Another sample with a diameter of 12 mm (cross-sectional area A = 1.13 cm²) was used. 2 A circular negative electrode sample with a thickness t of 0.01 cm was immersed in electrolyte until saturated, and then assembled into a symmetrical cell with a blocked electrode. The R value was obtained by AC impedance testing. b It is 21.3Ω. According to κ_eff = t / (R b × A) Calculation yields κ_eff = 0.010 cm / (21.3Ω × 1.13 cm) 2 =0.4154 mS / cm. According to the formula for C of McMalin number M: M=C×κ0 / κ_eff= (9.53 / 0.4154)× 0.35=8.02 ≈8.
[0068] Examples 2-18 Examples 2-18 are basically the same as Example 1, the main difference being the composition of the electrolyte and / or the porosity and McMurlin number of the negative electrode. The composition of the electrolyte is shown in Table 1.
[0069] Comparative Examples 1-7 It is basically the same as Example 1, except that the composition of the electrolyte is different. The composition of the electrolyte is shown in Table 1.
[0070] In the above embodiments and comparative examples, in order to obtain negative electrode sheets with different porosities and McMurline numbers, the parameters of high-speed shearing during the preparation of the negative electrode sheet in Example 1 can be adjusted. That is, within the range of a linear velocity of 15-20 m / s and a high-speed shearing time of 10-20 minutes, adjusting the corresponding linear velocity and high-speed shearing time can obtain embodiments with different porosities and McMurline numbers than in Example 1.
[0071] In Table 1, the porosity and McMarin number were determined using the corresponding methods described in Example 1.
[0072] In Table 1, the electrolyte salts used in each example and comparative example are NaPF6 and NaFSI, and the mass percentage of NaPF6 and NaFSI in the electrolyte is 7%.
[0073] Table 1. Composition of sodium-ion batteries in the examples and comparative examples
[0074] The performance of sodium-ion batteries prepared in the examples and comparative examples was measured in the present invention, and the measurement methods are as follows: -10℃ Cyclic Performance Test: At -10℃, the battery was charged to 3.95V at a constant current and constant voltage of 0.2C with a cutoff current of 0.05C, and then discharged to 2V at a constant current of 0.5C. This is the first cycle. The battery was charged / discharged under the above conditions until 80% capacity retention was achieved. The number of cycles when the battery retained 80% of its capacity at -10℃ was calculated.
[0075] 25 / 45℃ Cycling Performance Test: At 25 / 45℃, the above battery was charged to 3.95V at 1C constant current and constant voltage with a cutoff current of 0.05C, and then discharged to 2V at 1C constant current. This is the first cycle. Cycling and discharging were performed under the above conditions until 80% capacity retention was achieved. The impedance growth rate of the battery after cycling at 25 / 45℃ was calculated as follows: Impedance growth rate (%) = [(Internal resistance after 500 cycles - Internal resistance after the first cycle) / Internal resistance after the first cycle] × 100%. The group that reached 80% capacity retention in less than 500 cycles was recorded as the impedance growth rate when reaching 80% capacity retention.
[0076] The results are shown in Table 2: Table 2 Performance tests of sodium-ion batteries in the examples and comparative examples
[0077] The data analysis in Table 2 is as follows: 1. The content and ratio of sodium salt additive A and sulfur-containing additive B play a decisive role in the interfacial stability of the battery.
[0078] Sodium salt additive (A): In Example 2 (A=1%), compared to Example 1 (A=0.5%), increasing the sodium salt additive content increased the -10°C cycle count from 1013 to 1144, indicating that an appropriate amount of sodium salt additive can significantly improve low-temperature kinetics. However, Comparative Example 7 (A=3%) had an excessively high content, leading to abnormal cycling, such as a sharp drop in the low-temperature cycle count to 59. This verifies that excessive sodium salt additive can restrict dissolution and form crystals, harming battery performance. Comparative Example 1 lacked sodium salt additive, resulting in insufficient SEI film formation and a significant decrease in cycle performance. Sulfur-containing additive (B): Comparative Example 2, lacking a sulfur-containing additive (B=0), exhibited a high impedance growth rate of 506.4% after 500 cycles at 45°C, with only 425 cycles at 45°C. This indicates that the sulfur-containing additive plays an irreplaceable role in improving the high-temperature stability of the SEI film and inhibiting electrolyte decomposition. Comparative Example 6 (B=3.0%) increased the PCS content to 3.0%, resulting in a decrease in the number of cycles at 45°C to 3751.0, while the impedance growth rate remained high at 485.0%. This suggests that excessive sulfur-containing additive content leads to an excessively thick interfacial film, increasing initial impedance and exacerbating gas production, thereby deteriorating high-temperature performance. With a B content of 1.0%, different types of sulfur-containing additives were compared: Example 4 (PCS), Example 6 (MMDS), Example 7 (PS), and Example 8 (DTD). Among them, Example 8 (DTD) exhibited the best overall performance, achieving a low-temperature cycle count of 1280.0 and the lowest impedance growth rate at 45°C at 129.8%. This demonstrates that DTD, as a sulfur-containing additive, has significant advantages in constructing stable SEI films over a wide temperature range.
[0079] 2. The porosity C and McMallin number M of the negative electrode sheet together determine the ion transport efficiency inside the electrode sheet.
[0080] Comparing Examples 4 (C=35%), 9 (C=25%), and 10 (C=50%), Example 4 exhibits the best balance. Too low a porosity (Example 9) resulted in only 706 low-temperature cycles, limiting ion transport; while too high a porosity (Example 10), although improving low-temperature performance, resulted in a 180.4% increase in impedance at 45°C, leading to a performance decrease. Comparative Example 3 (C=20%) had too low a porosity, resulting in a higher initial impedance (3.64 mΩ) and more limited low-temperature performance (444 cycles). This indicates that the optimal balance is achieved around 35% C.
[0081] 3. The McMarin number M characterizes the tortuosity of the ion transport path.
[0082] In Example 18 (M=4.0), compared to Example 4 (M=8.0), the lower M value resulted in an increased number of low-temperature cycles to 1388, and the impedance growth rate at 45°C decreased to 100.2%, demonstrating excellent performance at M=4. However, when the M value was too high, as in Comparative Example 5 (M=30.0), the calculated value (5.652) far exceeded the upper limit, the ion transport path became too tortuous, and the number of low-temperature cycles was only 291, resulting in extremely poor performance. Furthermore, it was found during the fabrication process that it was difficult to obtain negative electrode sheets with an M value lower than 4, leading to poor availability and high manufacturing costs. This invention couples C and M through a formula, ensuring optimal ion channel conductivity while maintaining high energy density and feasibility.
[0083] In summary, Examples 1-19 that satisfy the above relationships all exhibit excellent cycling performance (comprehensive performance of the above indicators) at different temperatures.
[0084] Therefore, the present invention limits 2.1 ≤ C / [100×(A+B)] + M 1 / 2 ≤ 5.2, where A is the mass percentage of sodium salt additives in the electrolyte, 0.1%≤A≤2%; B is the mass percentage of sulfur-containing additives in the electrolyte, 0.1%≤B≤2%; C is the porosity of the negative electrode sheet, 25%≤C≤50%; and M is the McMahring number of the negative electrode sheet, 4≤M≤25. A deep match between the electrolyte chemical composition and the physical structure of the negative electrode sheet was successfully achieved. This synergistic design not only ensures the sodium-ion battery has a high energy density but also effectively reduces the initial impedance and impedance growth rate at high temperatures, significantly improving the long-cycle stability of the sodium-ion battery over a wide temperature range (-10℃ to 45℃). Experimental results fully demonstrate that only when all parameters are within the range defined by this invention can a wide-temperature excellent sodium-ion battery with low initial impedance, good low-temperature permeability, and stable high-temperature performance be obtained.
[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A sodium-ion battery, characterized in that, The sodium-ion battery comprises a positive electrode, a negative electrode, and an electrolyte, wherein the electrolyte includes sodium salt additives and sulfur-containing additives, and the sodium-ion battery satisfies the following relationship: 2.1≤C / [100×(A+B)]+M 1 / 2 ≤5.2; In the formula: A represents the mass percentage of sodium salt additives in the electrolyte, where 0.1% ≤ A ≤ 2%. B represents the mass percentage of sulfur-containing additives in the electrolyte, where 0.1% ≤ B ≤ 2%. C is the porosity of the negative electrode sheet, where 25% ≤ C ≤ 50%; M is the McMarin number of the negative electrode, where 4 ≤ M ≤ 25.
2. The sodium-ion battery according to claim 1, characterized in that, The sodium-ion battery satisfies the following relationship: 2.4 ≤ C / [100×(A+B)]+M 1 / 2 ≤3.4; 0.5%≤A≤1.0%, 0.5%≤B≤1.0%, 35%≤C≤50%, 5≤M≤10.
3. The sodium-ion battery according to claim 1 or 2, characterized in that, The mass ratio of the sodium salt additive to the sulfur-containing additive is 0.33~3.0:
1.
4. The sodium-ion battery according to any one of claims 1 to 3, characterized in that, The sulfur-containing additive includes at least one of cyclic sulfate compounds and cyclic sulfonate compounds; Preferably, the cyclic sulfate compounds include at least one selected from ethylene sulfate, propylene sulfate, 4-methylethylene sulfate, 4-fluoroethylene sulfate, 4,4'-diethylene sulfate, spirodiDTD, bis(DTD), 4,5-dimethylethylene sulfate, and 1,2-cyclopentadiene sulfate. Preferably, the cyclic sulfonate compound includes at least one of 1,3-propanesulfonate lactone, 1,3-propenesulfonate lactone, and methanedisulfonate methylene ester; Preferably, the sulfur-containing additive is selected from at least one of ethylene sulfate, propylene sulfate, 1,3-propanesulfonate lactone, 1,3-propenesulfonate lactone, and methanedisulfonate.
5. The sodium-ion battery according to any one of claims 1 to 4, characterized in that, The sodium salt type additive includes at least one of sodium oxalate borate, sodium difluorophosphate, sodium difluorodioxalate phosphate, and sodium fluorosulfonate; the sodium oxalate borate includes sodium bis(oxalate borate). Preferably, the sodium salt additive is selected from at least one of sodium fluorosulfonate and sodium difluorodioxazophosphate.
6. The sodium-ion battery according to any one of claims 1 to 5, characterized in that, The electrolyte also includes ester solvents, which include cyclic carbonate solvents, chain carbonate solvents and linear carboxylic acid ester solvents in a volume ratio of 20~40:20~40:10~60. Preferably, the cyclic carbonate solvent includes at least one of ethylene carbonate, propylene carbonate, and γ-butyrolactone; Preferably, the chain carbonate solvent includes at least one of dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate; Preferably, the linear carboxylic acid ester solvent includes at least one of methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, and methyl butyrate. Preferably, the ester solvent is composed of propylene carbonate, ethyl methyl carbonate and ethyl acetate.
7. The sodium-ion battery according to any one of claims 1 to 6, characterized in that, The electrolyte also includes an electrolyte salt, wherein the electrolyte salt has a mass percentage content of 10-15% in the electrolyte; Preferably, the electrolyte salt includes at least one of sodium hexafluorophosphate, sodium tetrafluoroborate, sodium perchlorate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethanesulfonyl)imide. Preferably, the electrolyte salt is composed of sodium hexafluorophosphate and sodium difluorosulfonamide in a mass ratio of 0.5 to 2:
1.
8. The sodium-ion battery according to any one of claims 1 to 7, characterized in that, The electrolyte also includes conventional additives, wherein the conventional additives constitute 0.5% to 2.5% of the electrolyte by mass. Preferably, the conventional additives include at least one of vinylene carbonate, fluoroethylene carbonate, vinyl ethylene carbonate, and sodium difluorooxalate borate. Preferably, the conventional additive is composed of sodium difluorooxalate borate and fluoroethylene carbonate in a mass ratio of 1:1 to 3.
9. The sodium-ion battery according to any one of claims 1 to 8, characterized in that, The negative electrode sheet includes a negative current collector and a negative active material layer formed on the surface of the negative current collector. By mass percentage, the negative electrode slurry used to form the negative active material layer includes 93-97% negative active material, 0.5-5% negative conductive agent, 0.5-5% negative thickener, and 0.5-3% negative binder.
10. The method for preparing a sodium-ion battery according to any one of claims 1 to 9, characterized in that, Includes the following steps: After assembling the positive electrode, separator, and negative electrode into a bare cell, the electrolyte is injected, followed by encapsulation and formation processes.
Citation Information
Patent Citations
Ultralow-temperature high-energy-density sodium ion battery and preparation method thereof
CN117976978A
